“EXPLORING THE CONTROVERSIAL LINK BETWEEN ARTIFICIAL SWEETENERS AND CANCER RISK: A NARRATIVE REVIEW” - Dr. Hafsa Niazi; Dr. Nadia Nahal; Dr. Huzaira Zainab; Dr. Tehniat Bashir; Dr. Syed Hassnain Zafar Bukhari; Dr. Aousaf Ahmed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Aspartame is a widely consumed non-sugar sweetening agent used in more than ninety different countries. It is a methoxycarbonyl of apeptidyl of aspartic acid and phenylalanine. It is many times more saccharine than sugar but has very less calories therefore it is widely used in diet or zero-sugar food products. When metabolized in our body it is broken down into diketopiperazine, aspartyl phenylalanine, and phenylalanine. It is a frequently used and studied synthetic sweetening agent. However, there is a controversy related to its possible carcinogenic effect. Some studies have shown it to have some genotoxic and carcinogenic effects. But others have shown no genotoxic or carcinogenic effects of aspartame when ingested. The possible carcinogenic effect of aspartame is controversial for a long time. As aspartame is widely used in daily use dietary products, finding out whether it is safe for human consumption is extremely important. This literature review/study’s sole objective is to know about aspartame’s possible carcinogenic roles. The search engine used to find articles related to the possible carcinogenic effects of aspartame is PubMed. The keywords used for searching the articles are; aspartame, carcinogenesis, metabolism of aspartame in humans, aspartame as a carcinogen, genotoxicity, genotoxicity induced by aspartame, and artificial sweeteners. The articles are further filtered by the timeline (articles from 2013 – 2023 only). Articles from only the past 10 years are included, which consist of systemic reviews, meta-analyses, research articles, and literature reviews. 27 articles are studied.